Colloidal assembly by ice templating - Kumaraswamy, Guruswamy; Biswas, Bipul; Choudhury, Chandan Kumar (Faraday Discussions, 2016)
We investigate ice templating of aqueous dispersions of polymer coated colloids and crosslinkers, at particle concentrations far below that required to form percolated monoliths. Freezing the aqueous dispersions forces the particles into close proximity to form clusters, that are held together as the polymer chains coating the particles are crosslinked. We observe that, with an increase in the particle concentration from about 106 to 108 particles per ml, there is a transition from isolated single particles to increasingly larger clusters. In this concentration range, most of the colloidal clusters formed are linear or sheet like particle aggregates. Remarkably, the cluster size distribution for clusters smaller than about 30 particles, as well as the size distribution of linear clusters, is only weakly dependent on the dispersion concentration in the range that we investigate. We demonstrate that the main features of cluster formation are captured by kinetic simulations that do not consider hydrodynamics or instabilities at the growing ice front due to particle concentration gradients. Thus, clustering of colloidal particles by ice templating dilute dispersions appears to be governed only by particle exclusion by the growing ice crystals that leads to their accumulation at ice crystal boundaries.

Linking catalyst-coated isotropic colloids into ``active'' flexible chains enhances their diffusivity - Biswas, Bipul; Manna, Raj Kumar; Laskar, Abhrajit; Kumar, P. B. Sunil; Adhikari, Ronojoy; Kumaraswamy, Guruswamy (ACS Nano, 2017)
Active colloids are not constrained by equilibrium: ballistic propulsion, superdiffusive behavior, or enhanced diffusivities have been reported for active Janus particles. At high concentrations, interactions between active colloids give rise to complex emergent behavior. Their collective dynamics result in the formation of several hundred particle-strong flocks or swarms. Here, we demonstrate significant diffusivity enhancement for colloidal objects that neither have a Janus architecture nor are at high concentrations. We employ uniformly catalyst-coated, viz. chemo-mechanically, isotropic colloids and link them into a chain to enforce proximity. Activity arises from hydrodynamic interactions between enchained colloidal beads due to reaction-induced phoretic flows catalyzed by platinum nanoparticles on the colloid surface. This results in diffusivity enhancements of up to 60% for individual chains in dilute solution. Chains with increasing flexibility exhibit higher diffusivities. Simulations accounting for hydrodynamic interactions between enchained colloids due to active phoretic flows accurately capture the experimental diffusivity. These simulations reveal that the enhancement in diffusivity can be attributed to the interplay between chain conformational fluctuations and activity. Our results show that activity can be used to systematically modulate the mobility of soft slender bodies.
Keywords: active matter; Brownian motion; colloidal assembly; diffusivity; ice templating

Colloidal assembly by directional ice templating - Biswas, Bipul; Misra, Mayank; Bisht, Anil Singh; Kumar, Sanat K.; Kumaraswamy, Guruswamy (Soft Matter, 2021)
We investigate directional ice templating of dilute aqueous colloidal particle dispersions and examine the nature of the assemblies that result. We coat micron-size polystyrene colloids with cross-linkable polymer (polyethyleneimine, PEI), add cross-linker, and subject this dispersion to unidirectional freezing. We work at sufficiently low colloid concentrations, such that the particles do not percolate on freezing. When the aqueous dispersion freezes, ice crystals force polymer-coated particles and cross-linker into close proximity. This results in the formation of cross-linked clusters of particles at ice crystal boundaries. We vary the particle volume fraction from phi similar to 2.5 x 10(-3) to phi similar to 5.0 x 10(-2) and observe that there is a transition from isolated single particles to increasingly large sized clusters. Most of the clusters formed under these conditions are either linear, two-particle wide chains, or sheet-like aggregates. The probability (P-n) of clusters containing n particles (n > 2) obeys a power law P-n similar to n(-eta), where eta strongly depends on the particle concentration in the dispersion, varying from 2.10 (for phi similar to 5.0 x 10(-2)) to 3.03 (for phi similar to 2.5 x 10(-3)). This change in eta is qualitatively different from the case of isotropic freezing, where eta is particle concentration-independent and depends only on the ice nucleation density. To understand the differences between isotropic and directional ice templating, we performed lattice simulations of a highly simplified model, where ice crystals grow at a constant rate to force clustering. We ignore hydrodynamic interactions and ice growth instabilities. Despite ignoring these experimental details, the simulations capture the experimental results, nearly quantitatively. As the ice crystals grow and the space available to the colloids ``closes up'' so that the particles cluster to form aggregates, crystallization protocol-induced differences in the geometry of these ``closed up'' spaces determine the scaling behaviour of P-n.

Elastic piezoelectric aerogels from isotropic and directionally ice-templated cellulose nanocrystals: comparison of structure and energy harvesting - Ram, Farsa; Biswas, Bipul; Torris, Arun; Kumaraswamy, Guruswamy; Shanmuganathan, Kadhiravan (Cellulose, 2021)
We report the preparation of highly compressible and elastic piezoelectric aerogels of carboxylated cellulose nanocrystals (CNCs). Aqueous CNC dispersions containing polyethyleneimine and crosslinker were frozen isotropically to yield isotropic aerogels, while oriented aerogels were prepared by directional freezing. These aerogels were highly flexible and porous (similar to 85% void fraction), exhibiting greater than 90% recovery at 50% compressive strain even after 100 compression-decompression cycles. Since such aerogels with low bulk modulus and high anisotropy would be an ideal platform for leveraging the piezoelectric properties of CNCs, we used them to prepare piezoelectric nanogenerator devices and determined their energy transduction behavior. Anisotropic aerogels led to an enhanced open-circuit voltage of 840 mV (at similar to 8 N applied force), which is over 2.6 times higher than isotropic aerogels (320 mV). The energy density of anisotropic aerogels was around 52 nW/cm(2), representing outstanding piezoelectric performance for cellulose-based aerogels. Such aerogels with high compressibility, elastic recovery and exceptional piezoelectric performance could have potential applications in sensors, wearable electronics, etc.
Keywords: Aerogel; Anisotropic; Cellulose nanocrystals; energy harvesting; Piezoelectricity

Rigidity dictates spontaneous helix formation of thermoresponsive colloidal chains in poor solvent - Biswas, Bipul; Mitra, Debarshi; KP, Fayis; Bhat, Suresh; Chatterji, Apratim; Kumaraswamy, Guruswamy (ACS Nano, 2021)
The formation of helical motifs typically requires specific directional interactions. Here, we demonstrate that isotropic interparticle attraction can drive self-assembly of colloidal chains into thermo-reversible helices, for chains with a critical level of backbone rigidity. We prepare thermoresponsive colloidal chains by cross-linking PNIPAM microgel-coated polystyrene colloids (“monomers”), aligned in an AC electric field. We control the chain rigidity by varying cross-linking time. Above the LCST of PNIPAM, there is an effective attraction between monomers so that the colloidal chains are in a bad solvent. On heating, the chains decrease in size. For the most rigid chains, the decrease is modest and is not accompanied by a change in shape. Much less rigid chains form relatively compact structures, resulting in a large increase in the local monomer density. Unusually, chains with intermediate rigidity spontaneously assemble into helical structures. The chain helicity increases with temperature and plateaus above the collapse transition temperature of the microgel particles. We simulate a minimal model that captures the spontaneous emergence of the helical conformations of the polymeric chain and provides insight into this shape transition. Our work suggests that a purely mechanical instability for semiflexible filaments can drive helix formation, without the need to invoke directional interactions.